Circumstances that are subject to clarification at the initial stage of the investigation of medicinal products counterfeit and circulation of counterfeit medicinal products - Shepilov, O. O. (Аналітично-порівняльне правознавство, 2025)
The article is devoted to the study of the circumstances that are subject to clarification at the initial stage of the investigation of the falsification of medicines and the circulation of falsified medicines. It is established that the circumstances that are subject to clarification in the process of investigating criminal offenses, including the falsification of medicines and the circulation of falsified medicines, constitute an integral part of a separate forensic methodology, since their establishment occurs at each stage of the pre-trial investigation. Their content is determined, first of all, by the subject of proof, the legal structure of the crime, enshrined in the Criminal Code of Ukraine, as well as the peculiarities of the mechanism of committing the relevant criminal offense. It is noted that during the investigation of the falsification of medicines and the circulation of falsified medicines, the circumstances that are subject to clarification include the following: 1) provided for by Art. 91 of the Criminal Procedure Code of Ukraine; 2) established by the disposition of Art. 321-1 of the Criminal Code of Ukraine; 3) which are of importance for the consideration of the case on the merits, but are not included in the subject of evidence. It was established that the Ministry of Health of Ukraine does not provide publicly available statistical information on the number of patients who suffered as a result of the use of falsified medicines, in particular, there is no data on cases of fatal consequences. The calculation of economic losses caused to the state and legal manufacturers of medicines as a result of the circulation of low-quality pharmaceutical products is also not carried out. And the public is not provided with information on the losses of budget funds aimed at eliminating the consequences of the use of such drugs by patients. In addition, it was concluded that at the initial stage of the investigation of the falsification of medicines and the circulation of falsified medicines, the circumstances provided for in clauses 1, 2, part 1, article 91 of the Criminal Procedure Code of Ukraine will be subject to clarification, namely: 1) the event of the criminal offense (time, place, method and other circumstances of the commission of the criminal offense); 2) the guilt of the accused in committing a criminal offense, the form of guilt, the motive and purpose of committing the criminal offense.